Effect of pressure on the Fermi surface and electronic structure of ErGa₃ - Pluzhnikov, V.B.; Grechnev, G.E.; Fomenko, Yu.V.; Czopnik, A.; Eriksson, O. (Физика низких температур, 1999)
The Fermi surface and cyclotron masses of the ErGa₃ compound are studied by means of the de Haas-van Alphen technique under pressure. Concurrently, the electronic structure is calculated ab initio for the ferromagnetic phase of ErGa₃. The experimental data have been analyzed on the basis of the calculated volume-dependent band structure and compared with available results for isostructural TmGa₃ and LuGa₃ compounds.